Possible meanings in religious pluralism (RuMoRes, 2014)
This article derives from the research project entitled In the name of a plural faith: the religious diversity in Globo Network’s television show Sagrado. We have analyzed on it the impact of religious pluralism within the local context. Through deep interviews, the reception research pointed out what Martín Barbero (2009) calls the “wide market of communicational offers”. The results of the study indicate that the television show Sagrado (Sacred) plays an important role in spreading major religious strands, but it’s length is insufficient to influence the public’s identity formation and for an in-depth debate.